2019
DOI: 10.21203/rs.2.18845/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-rheumatic treatment and prosthetic joint infection: An observational study in 494 elective hip and knee arthroplasties.

Abstract: Abstract Background Surgical site infections are more frequent among patients with rheumatic disease. To which extent this is related to immunosuppressive antirheumatic drugs is unclear, as is the value of discontinuing medication perioperatively.Objectives To assess the rate of surgical site infections after knee and hip-replacement in patients with inflammatory joint disease, with emphasis on periprosthetic joint i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This conditional recommendation now includes apremilast, but it is otherwise unchanged from the 2017 guideline. Four observational studies provided additional indirect evidence to the previous systematic literature review and found no relationship between the included drugs and the risk of postoperative infections, although the number of included cases and events were low (11,(27)(28)(29). Patients with a history of severe or recurrent infections or prior prosthetic joint infection may elect to withhold these medications before surgery.…”
Section: Recommendationsmentioning
confidence: 97%
“…This conditional recommendation now includes apremilast, but it is otherwise unchanged from the 2017 guideline. Four observational studies provided additional indirect evidence to the previous systematic literature review and found no relationship between the included drugs and the risk of postoperative infections, although the number of included cases and events were low (11,(27)(28)(29). Patients with a history of severe or recurrent infections or prior prosthetic joint infection may elect to withhold these medications before surgery.…”
Section: Recommendationsmentioning
confidence: 97%
“…The role of anti-RA drugs in infection susceptibility has been studied and did not show a significant increase in the rate of infection. 26 Active cortisone treatment is the only medication that substantially poses the patient at risk of a devastating infection. 3,17…”
Section: Figurementioning
confidence: 99%
“…To date, there is no clear evidence of whether or when to stop (and restart) bDMARDs during the perioperative period, with some studies concluding that bDMARDs could be safely continued [18][19][20] and others reporting an increased risk of infection with continued use 21,22 . A systematic review 23 comparing patients who continued with those who withheld bDMARDs perioperatively found a reduced risk of infection among those who withheld; however, this analysis was limited to data obtained from 3 studies, and additional studies have since been published 20,[24][25][26][27][28][29] .…”
mentioning
confidence: 99%